Circadian rhythms have no effect on cycling performance - Dalton, B.; McNaughton, L.; Davoren, B. (International Journal of Sports Medicine, 1997)
The aim of this research was to determine if circadian rhythms have an effect on time trial cycling performance of 15 min duration. Seven males (Mean+/-SD): age, 22.3+/-4.9 yr; height 179.0+/-7.9 cm, body mass 74.5+/-15.5 kg; VO2max 68.0+/-5.7 ml x kg(-1) x min(-1) who were all competitive cyclists or triathletes with previous experience in laboratory testing procedures volunteered to participate in this study. Each of the seven subjects underwent a series of four tests; one VO2 max test, and three 15 min maximal performance tests, at varying times during a 24 hr period. Testing times were at 08.00-10.00; 14.00-16.00 and 20.00-22.00 hours. Heart rate was recorded during the last 10-15 seconds of each minute and blood lactate levels were taken at 5 and 10 min during exercise and again immediately post-exercise. O2 consumption was measured continuously using open circuit spirometry. RPE was measured using the Borg scale at 5 and 10 min during, and again immediately following the completion of testing. Resting oral temperature was the only variable to show a significant time of day effect (p<0.05). Oral temperature during the afternoon was higher than both morning and evening results by 0.76 degrees C and 0.09 degrees C respectively. Total work (kJ) and average power output (W) were recorded at their highest during the morning session and reached a trough during the afternoon session, but these differences were not significant (p = 0.9997 and 0.9972 respectively). The results obtained in this study indicate that while certain biological rhythms are present, they appear to have no effect on this type of cycling performance. Although athletic performance may be enhanced by training programs that are compatible with an individuals body clock, the ability to perform and train at various times has an adaptive response which appears to over-ride these naturally inherent rhythms.